Effectiveness of gargle with extract oyster mushroom (pleurotus spp) to forming plaque in ecc patients (early childhood caries) - Pharadiba; Anisa N. Ferry; Atika B. Ferry; Fajriani (DiscoverSys Inc., 2022)
Objective: this study have aims to look at the effectiveness of gargling with extract oyster mushroom (pleurotus ostreatus) on forming plaque in ECC ( Early Childhood Caries ) patient. Material and Method: This study was conducted in Sudiang Asri Islamic kindergarten children in April-May 2018. This study used a pretestposttest design with a control group. A total sample is 90 person suffering from ECC. The sample was divided into three groups, namely Chlorhexidine gluconant 0.2%, Aquadest Steril and solution of oyster mushroom extract concentration of 50%. The score were measured using the Grenee and Vermillion methods about before and after the intervention. Analysis data use SPSS version 22.0 for windows. Results: The result of the independent t – test that showed different significant about before and after the treatment of oyster mushroom extract (pleurotus ostreatus) (p<0,05). The result of index debris on chlorhexidine gluconant 0,2% in the pre test of 1.681 ± 0.538, and in the post test of 1.486 ± 0.429. Debris index result on sterill Aquadest in the pre test was 1.492 ± 0.498 and in the post test was 1.486 ± 0.429. While the debris index result in a solution of 50% oyster mushroom extract in the pre test of 1.813 ± 0.447 and in the post test of 1.513 ± 0.483. Conclusion: Giving a gargle solution with oyster mushroom extract (pleurotus ostreatus) can inhibit dental plaque.